Norwegian midwives' perceptions of their practice environment: A mixed methods study - Mirjam Lukasse; Lena Henriksen (Wiley, 2019)
Abstract Aim To investigate Norwegian midwives' perceptions of their working environment. Design A nationwide postal survey in 2014 collected information from 489 midwives, including the Practice Environment Scale and seven open‐ended questions concerning the workplace. Methods Psychometric‐, descriptive‐ and comparative analysis was used for the quantitative data and content analysis for the qualitative data. Results Psychometric analyses yielded five subscales: Quality of management; Resource adequacy; Midwife‐doctor relations; Opportunities for development; and Midwifery foundation for care. Content analyses identified four main themes: Lack of resources; Insufficient support; Staying in midwifery; and Lack of influence. Subthemes only found in the qualitative analysis were as follows: Fear of adverse events and The strain of shift work. Most midwives rated the PES subscales Midwife‐doctor relations and Quality of management favourable. In contrast, the theme Lack of influence showed that midwives felt powerless in a constantly changing work environment and ruled by the medical model of care.